2019
DOI: 10.1186/s13041-019-0471-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plasma microRNA expression changes in multiple system atrophy and Parkinson’s disease

Abstract: MicroRNAs (miRNAs) are endogenous small (18–25 nt), single-stranded, non-coding RNAs that play key roles in post-transcriptional gene expression regulation. The expression profiles of miRNAs in biofluids and tissues change in various diseases. Multiple system atrophy (MSA) and Parkinson’s disease (PD) are both categorized as α-synucleinopathies and often present with similar clinical manifestations. This study aimed to identify miRNAs that are differently expressed in plasma samples of PD patients, MSA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 44 publications
(36 reference statements)
2
42
0
1
Order By: Relevance
“…Moreover, we also found that the expression profile in MSA-P seemed to share more gene sets with PD than with MSA-C, possibly in relation to clinical similarities. In line with our findings, a recent microRNA study 21 has also reported differential deregulation of microRNAs between the two MSA subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we also found that the expression profile in MSA-P seemed to share more gene sets with PD than with MSA-C, possibly in relation to clinical similarities. In line with our findings, a recent microRNA study 21 has also reported differential deregulation of microRNAs between the two MSA subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…One study dissected that miR-19b-3p is significantly decreased in exosomes derived from cerebrospinal fluid in the patients with Parkinson’s disease (PD) 2 . However, another study elucidated that plasma miR-19b-3p level is higher in the PD patients compared with healthy persons and multiple-system atrophy (MSA) patients, indicating that miR-19b-3p could be involved in pathophysiology or symptoms of PD and MSA 3 . Notably, miR-19b-3p is reported to be a potential candidate for prediction of autism spectrum disorder (ASD) 4 .…”
mentioning
confidence: 99%
“…The level of miR-24 expression is dysregulated in the serum of patients with MSA [202,203]. Interestingly, miR-24 binds to the 3 -UTR of Per2 and plays an important post-transcriptional regulatory role in the PER2 expression required for normal circadian timekeeping, as described above.…”
Section: Multiple System Atrophymentioning
confidence: 80%